(untitled) (Società e diritti, 2022)
The political management of the health crisis has forcefully posed to legal theory and political philosophy the classic question of the relationship between institutional normality and the emergence of political intervention. What has happened has prompted part of the doctrine to use the concept of a state of exception and in some cases to denounce the nonchalant use of extra-ordinem powers that have strained the democratic fabric of our communities. Upon close examination of the legal-constitutional contours involved, the thesis of the illegitimacy of some measures taken by government authorities seems well-founded, and a re-examination of what happened in the previous two years seems increasingly necessary.